Prominent microglial activation in cortical white matter is selectively associated with cortical atrophy in primary progressive aphasia. (17th May 2018) - Ohm, D. T.; Kim, G.; Gefen, T.; Rademaker, A.; Weintraub, S.; Bigio, E. H.; Mesulam, M.‐M.; Rogalski, E.; Geula, C.
Abstract : Aims: Primary progressive aphasia (PPA) is a clinical syndrome characterized by selective language impairments associated with focal cortical atrophy favouring the language dominant hemisphere. PPA is associated with Alzheimer's disease (AD), frontotemporal lobar degeneration (FTLD) and significant accumulation of activated microglia. Activated microglia can initiate an inflammatory cascade that may contribute to neurodegeneration, but their quantitative distribution in cortical white matter and their relationship with cortical atrophy remain unknown. We investigated white matter activated microglia and their association with grey matter atrophy in 10 PPA cases with either AD or FTLD‐TDP pathology. Methods: Activated microglia were quantified with optical density measures of HLA‐DR immunoreactivity in two regions with peak cortical atrophy, and one nonatrophied region within the language dominant hemisphere of each PPA case. Nonatrophied contralateral homologues of the language dominant regions were examined for hemispheric asymmetry. Results: Qualitatively, greater densities of activated microglia were observed in cortical white matter when compared to grey matter. Quantitative analyses revealed significantly greater densities of activated microglia in the white matter of atrophied regions compared to nonatrophied regions in the language dominant hemisphere ( P < 0.05). Atrophied regions of the language dominant hemisphere also showed significantly more activated microglia compared to contralateral homologues ( P < 0.05). Conclusions: White matter activated microglia accumulate more in atrophied regions in the language dominant hemisphere of PPA. While microglial activation may constitute a response to neurodegenerative processes in white matter, the resultant inflammatory processes may also exacerbate disease progression and contribute to cortical atrophy.